Liquidity, Leverage, and Asset Utilization as Determinants of Profitability: Evidence from Indonesian Transportation Sector Firms (2019–2020, 2022–2023) (International Journal of Economics Management and Social Science, 2026)
This study investigates whether liquidity, leverage, and asset utilization explain profitability among transportation sector firms listed on the Indonesia Stock Exchange (IDX). Using secondary financial statement data for 15 firms over the years 2019, 2020, 2022, and 2023 (60 firm-year observations), profitability is proxied by return on assets (ROA), while liquidity is measured by the current ratio (CR), leverage by the debt-to-equity ratio (DER), and activity by total asset turnover (TATO). The dataset is analyzed using multiple linear regression with IBM SPSS Statistics (replicated with equivalent procedures). Descriptive statistics indicate substantial cross-firm dispersion, particularly for DER, reflecting heterogeneous capital structures and, in some cases, negative equity. The regression results show that CR and TATO have positive coefficients and DER has a negative coefficient, but none of the predictors are statistically significant at the 5% level. Classical assumption diagnostics suggest no serious multicollinearity and no evidence of heteroskedasticity, while residual normality is violated, implying that inference should be interpreted cautiously. Overall, the findings suggest that, during a period spanning pandemic and post‑pandemic recovery, profitability in the sampled transportation firms is influenced by factors beyond simple ratio-based liquidity, leverage, and efficiency measures. Keywords: current ratio; debt-to-equity ratio; total asset turnover; return on assets; transportation sector; Indonesia; financial ratio analysis